PENGARUH AKUNTABILITAS, KOMPETENSI, PROFESIONALISME, INTEGRITAS, DAN OBJEKTIVITAS AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT DENGAN INDEPENDENSI SEBAGAI VARIABEL MODERATING - Elen, Trismayarni; Mayangsari, Sekar (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
This research was to obtain empirical evidence on the influence of Accountability, Competence,Professionalism, Integrity, and Objectivity of Public Accountant to the quality of audit withindependence as Moderating Variable. The research was conducted by distributing questionnairesat several affiliated and non-affiliated registered public accountants located in Jakarta.Analysis model used to test the hypotheses was multiple linear regression, these analysis wasbased on valid questionnaires from 117 respondents. These research outcomes concluded thatthe accountability and integrity of partially significant effect on the quality of audit, while thecompetence, professionalism, and objectivity had no effect on audit quality partially. In addition,Â this research proved that accountability moderated by the independence significantly affected theÂ quality of the audit, while the competence, professionalism, integrity and objectivity moderatedby independence had no significant effect on the quality of the audit.